Physicochemical and Sensory Evaluation of Pomegranate Jam Enriched with Dragon Fruit Peel - Saifullizan, Nur Izzah Insyirah; Kormin, Faridah (Enhanced Knowledge in Sciences and Technology, 2025)
Pomegranate fruits, scientifically identified as Punica granatum L., are part of the Punicaceae family and are rich in bioactive chemicals, particularly polyphenols. Due to its high antioxidant and phytochemical content, as well as its numerous health benefits, pomegranate fruit is considered a ’super fruit’. Red dragon fruit, which is high in antioxidants, is processed into juice and peels for pectin extraction and natural food colouring, so increasing its nutritional value. Jams are fruit-based jams that are popular due to their sweetness and versatility. Cooking fruit pulp or puree with sugar and pectin produces an ideal consistency and texture. This study aimed to develop combination pomegranate with dragon fruit peel, evaluate sensory attributes and nutritional composition of the accepted product. The physicochemical properties of moisture content, colour, pH, total soluble solid, texture meanwhile, the nutritional composition of protein, fat, sodium, energy, total sugars, and carbohydrate were determined. Five different formulations were prepared, and the samples was optimized based on sensory evaluation by a panel of 40 panellists using a hedonic scale with 9 scale with seven attributes (appearance, colour, aroma, spreadibility, flavour, texture and overall acceptance). The physicochemical analyses revealed that the addition of dragon fruit peel significantly increased the moisture content (32.610±0.29%). The total soluble solids (0.660±0.005 °Brix), pH (2.423±0.12), and texture (firmness: 8.397±0.34 kg) were within acceptable ranges, with sample 1 exhibiting the best texture and overall sensory appeal. Nutritional analysis showed that sample 1 had higher levels of total sugar (41.7 mg/100 g), sodium (13 mg/100 g), energy (305 kcal/100 g), and protein (18.0 g/100 g), while maintaining a low-fat content (0.4 g/100 g). This study demonstrates the potential of using dragon fruit peel to enhance the nutritional and sensory qualities of pomegranate jam.